1987
DOI: 10.1128/aac.31.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Cephalosporin susceptibility of methicillin-resistant, coagulase-negative staphylococci

Abstract: Coagulase-negative staphylococci were tested for susceptibility to methicillin, cephradine, ceftriaxone, cephalothin, and cefamandole by standard broth microdilution. Most of the 26 methicillin-resistant isolates were susceptible to cephalothin and cefamandole, but very few were susceptible to ceftriaxone, and none was susceptible to cephradine. The proportion of bacterial cells that grew in the presence of 128 micrograms of methicillin per ml was calculated for each methicillin-resistant isolate. Those with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Yet, in some studies (11) cefamandole has been found to be effective clinically for a wide range of infections (excluding endocarditis) caused by methicillin-resistant staphylococci. Our data support the results of the latter studies, although cross-resistance between methicillin and cephalosporin agents with staphylococci (1,18) …”
Section: Methodssupporting
confidence: 83%
“…Yet, in some studies (11) cefamandole has been found to be effective clinically for a wide range of infections (excluding endocarditis) caused by methicillin-resistant staphylococci. Our data support the results of the latter studies, although cross-resistance between methicillin and cephalosporin agents with staphylococci (1,18) …”
Section: Methodssupporting
confidence: 83%
“…In contrast, cefamandole has not been consistently effective against methicillin-resistant staphylococci either in experimental models of infection (6) or in clinical studies (2,4). These discrepant results may be due to differences in degrees of methicillin resistance among strains of staphylococci (7). Recently Hartman and Tomasz identified three phenotypes of methicillin-resistant S. aureus: homogeneous, heterogeneous, and thermosensitive heterogeneous (5).…”
mentioning
confidence: 97%
“…Cross-resistance for methicillin and some cephalosporins has been demonstrated (Hansen-Nord et al, 1988;Menzies et al, 1987), with administration of cephalosporins increasing the acquisition of nosocomial MRSA three-fold (Asensio et al, 1996). Similarly, tetracycline resistance may be caused by one of several genes, one of which, tetK, is carried by a plasmid (pT181) that is inserted into SCCmecIII (Ito et al, 2003).…”
Section: B Environmental Reservoirs Of Mrsamentioning
confidence: 99%